Low-cost laparoscopic appendectomy in pediatric patients. Issue 3 (July 2016) - Ebeid, Abdel Mottaleb E.; Hassan, Hussam S.; Almetaher, Hisham A.; Elhalaby, Essam A.
Abstract : Background/purpose: Laparoscopic appendectomy is widely practiced worldwide and has become one of the commonly performed procedures in pediatric surgery practice. However, the cost effectiveness of the procedure remains a major concern. The present study aimed to evaluate the safety and effectiveness of the operative techniques used to reduce the cost of the procedure. Patients and methods: A prospective study was conducted on patients undergoing laparoscopic appendectomy over a period of 2 years. The techniques used to reduce the cost of laparoscopic appendectomy were as follows: (i) using reusable trocars instead of disposable ones; (ii) using monopolar electrogoagualtion to seal the mesoappendix instead of staplers, LigaSure, or Harmonic scalpels; and (iii) using a handmade loop to secure the base of the appendix instead of using endoloops. Results: This study included 39 boys and 21 girls. The median age was 10 years. The mean duration of the operation was 56.5 min. No intraoperative complications were encountered. Two cases developed pelvic hematoma and were managed conservatively with success. The mean hospitalization stay was 2 days. Conclusion: Division of the mesoappendix using monopolar electrocautry and closing the base of appendix using handmade endloops during laporoscopic appendectomy appears to be a simple, effective, safe, and cost-efficient technique. Therefore, the use of more costly instruments, such as the endostapler, LigaSure, or Harmonic scalpel, seems unwarranted.